OTOKHTONISASI EKONOMI ISLAM: PERSPEKTIF MAQĀSHID AL-SYARĪ´AH - Albani, Muhammad Syukri; Dayu, Wulan; Tamami, Ahmad; El Islamy, Imam (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2024)
This paper explores the concept of indigenization (otokhtonisasi) of Islamic economics, aiming to establish a framework that aligns with the authentic and original tenets of Islam. Indigenization is approached through two domains: practical Islamic economics, which focuses on implementing Islamic economic principles in daily life, and theoretical Islamic economics, which reflects on these principles to construct systemic models. Utilizing the lens of maqāṣid al-sharīʿah (objectives of Islamic law), this study identifies the integration of foundational principles such as hifz al-dīn (preservation of faith), hifz al-nafs (protection of life), hifz al-‘aql (protection of intellect), hifz al-nasl (preservation of lineage), hifz al-māl (protection of wealth), and expands to include hifz al-ummah (protection of society) and hifz al-bīʾah (protection of the environment). These principles underscore the necessity of aligning economic practices with spiritual, societal, and ecological well-being. The paper concludes that the development of Islamic economics must serve as a means (wasilah) to achieve comprehensive well-being (maslahah), maintaining harmony between individual and collective interests while fostering sustainability.